Erratum: Cassini, C.S., Cruz, C.A.G. & Caramaschi, U. (2010) Taxonomic review of Physalaemus olfersii (Lichtenstein & Martens, 1856) with revalidation of Physalaemus lateristriga (Steindachner, 1864) and description of two new related species (Anura: Leiuperidae). Zootaxa, 2491, 1–33. - Cassini, C. S.; Cruz, C. A. G.; Caramaschi, U. (Zootaxa, 2012)
It has been brought to our attention that we have erroneously referenced some numbers of the type series of Physalaemus feioi. Some type specimens were donated from the collection of the Museu de Zoologia João Moojen de Oliveira (MZUFV) to the collection of Museu Nacional (MNRJ). In the original publication we erroneously kept original MZUFV numbers while changing the collection acronym to MNRJ. The mistake could be noticed and corrected because MNRJ curators kept both numbers (MZUV and MNRJ) with every specimen. Thus, the composition of the type series remains the same, both amount and identity, and are corrected herein as follow. In the original description of P. feioi, pages 21 and 22, the lines designating holotype and paratypes should read (see the synopsis of the alterations in the Table 1):